2012
DOI: 10.1124/dmd.112.047746
|View full text |Cite
|
Sign up to set email alerts
|

UDP-Glucuronic Acid Binds First and the Aglycone Substrate Binds Second to Form a Ternary Complex in UGT1A9-Catalyzed Reactions, in Both the Presence and Absence of Bovine Serum Albumin

Abstract: ABSTRACT:The presence of bovine serum albumin (BSA) largely modulates the enzyme kinetics parameters of the human UDP-glucuronosyltransferase (UGT) 1A9, increasing both the apparent aglycone substrate affinity of the enzyme and its limiting reaction velocity (Drug Metab Dispos 39:2117-2129, 2011). For a better understanding of the BSA effects and an examination of whether its presence changes the catalytic mechanism, we have studied the enzyme kinetics of 4-methylumbelliferone glucuronidation by UGT1A9 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
8
2
Order By: Relevance
“…Similar effects were observed at both 1 and 2% BSA, suggesting that the effect could not be simply rationalized by the differential concentration ratio of microsomal protein to BSA. Current findings are in contrast to an increase in V max reported for other UGT1A9 substrates in the presence of BSA and at low microsomal protein concentrations (Manevski et al, 2011(Manevski et al, , 2012. However, differences in assay conditions in the published studies prevent direct comparison with the findings herein; further investigation is required to confirm whether these effects on V max are directly associated with the use of BSA at very low protein concentrations.…”
Section: Discussioncontrasting
confidence: 78%
“…Similar effects were observed at both 1 and 2% BSA, suggesting that the effect could not be simply rationalized by the differential concentration ratio of microsomal protein to BSA. Current findings are in contrast to an increase in V max reported for other UGT1A9 substrates in the presence of BSA and at low microsomal protein concentrations (Manevski et al, 2011(Manevski et al, , 2012. However, differences in assay conditions in the published studies prevent direct comparison with the findings herein; further investigation is required to confirm whether these effects on V max are directly associated with the use of BSA at very low protein concentrations.…”
Section: Discussioncontrasting
confidence: 78%
“…The reasoning was akin to that described for CYP2C9, whereby BSA was acting as a sink to bind free fatty acids released from the microsomal membranes during preparation, thus avoiding the competitive inhibition imparted by the fatty acids. Additional UGT/BSA studies conducted in a separate laboratory confirmed the effects of BSA on UGT2B7, and provided evidence that not only was the K m decreased, but the V max of UGT1A9 was also increased (Manevski et al, 2011(Manevski et al, , 2012.…”
Section: Advances In Reaction Phenotypingmentioning
confidence: 82%
“…This has been shown to work only for UGTs 1A1, 1A4 in microsomes but the data was not corroborated in Supersomes. It has also been documented for UGT1A9 in sf9 cell lysate supernatants but not validated in Supersomes or microsomes (101, 102). Moreover, there is no evidence yet that this is a valid method of inhibiting hepatic and other extra-hepatic UGTs either in microsomes or recombinant systems.…”
Section: Uridine Diphosphoglucuronosyl Transferasesmentioning
confidence: 99%